Mengenal Proses Terjadinya Pelangi pada Pebelajaran IPA di Sekolah Dasar (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
This study aims to understand how learning about rainbows can improve elementary school students' understanding of basic science concepts, particularly regarding the refraction of light and the color spectrum. The concept of rainbows is an important part of Natural Science (IPA) lessons because it involves optical phenomena that can be directly observed and related to students' daily experiences. In this study, the method used is a literature study, namely by collecting, reviewing, and analyzing various relevant library sources, such as scientific articles, textbooks, and educational journals that discuss the topic of science learning and the rainbow phenomenon. The results of this study indicate that learning about rainbows can be done through various interactive and fun approaches, such as through practical experiments using prisms, water droplets, or other simple media that can demonstrate the process of refraction of white light into a color spectrum. In addition, the use of visual media such as images, animated videos, and digital simulations has also proven effective in helping students understand the process of rainbow formation more concretely. Creative activities such as drawing rainbows, making color models, or role-playing as light and water droplets can also increase active student participation and make learning more enjoyable. This study also emphasizes the importance of integrating rainbow learning into the elementary school science curriculum systematically and contextually. Rainbow materials not only introduce scientific concepts in a fun way, but also develop critical thinking, observation, and experimental skills in children. With the right approach, this learning can foster students' interest in science from an early age. Therefore, the results of this study are expected to contribute positively to the development of more effective, creative, and developmentally appropriate science learning methods for elementary school students.